Very Early Response Evaluation by PET/MR in Patients with Lung Cancer—Timing and Feasibility - Natasha Hemicke Langer (Diagnostics, 2019)
Purpose: With the increasing number of therapy options available for patients with lung cancer, early response evaluation is needed. We performed this pilot study to assess the feasibility of early, repeated Positron emission tomography-magnetic resonance (PET/MR), the impact of timing and the capability for response prediction in lung tumors during chemotherapy. Methods: Patients with stage IV non-small cell lung cancer referred for chemotherapy were prospectively recruited. Fluorine-18-Fluorodeoxyglucose(18F-FDG)-PET/MR scans were performed prior to, during and after the first or second cycle of chemotherapy. Primary tumors were defined on all scans and size, FDG-uptake and apparent diffusion coefficient (ADC) were measured. Early response was described over time and a Standard Linear Mixed Model was applied to analyze changes over time. Results: 45 FDG-PET/MR scans were performed in 11 patients. Whereas the overall changes measured by ADC did not change significantly, there was an overall significant decrease in FDG-uptake from pre to post treatment scans. There was no difference in the FDG-uptake measured 1 or 3 weeks after therapy, but uptake measured 2 weeks after therapy differed from measurements at week 3. Changes measured in patients scanned during the first treatment cycle appeared more pronounced than during the second cycle. Conclusions: This pilot study indicates that response evaluation shortly after initiation of chemotherapy appears concordant with later evaluation and probably more reliable than evaluation midway between cycles. Responses during or after the first cycle of chemotherapy rather than during subsequent cycles are likely to be more readily measured.